Quartermaster supplies, equipment and services during operations in extreme cold. - Montgomery, John H. (Fort Leavenworth, KS : US Army Command and General Staff College, 1947)
This is a study of Quartermaster supplies, equipment, and services for use in operations where the temperatures may be as low as -20 degrees F. Consideration will be given to operations in both mountains and in the sub-arctic.